The Effect of Potato Protease Inhibitor II on Gastrointestinal Hormones and Satiety in Humans During Weight Reduction - Flechtner-Mors M (Dove Medical Press, 2020)
Marion Flechtner-Mors, 1 Ulrike Thoma, 2 Regina Wittmann, 2 Bernhard O Boehm, 2–4 Mona Mors, 1 Jürgen M Steinacker, 1 Uwe Schumann 1 1University Medical Center Ulm, Division of Sports and Rehabilitation Medicine, University Hospital Ulm, Ulm, Germany; 2Department of Internal Medicine I, University Hospital Ulm, Ulm, Germany; 3Lee Kong Chian School of Medicine, Nanyang Technological University Singapore, Singapore; 4Imperial College London, London, UKCorrespondence: Marion Flechtner-MorsDepartment of Internal Medicine II, Division of Sports and Rehabilitation Medicine, University Hospital Ulm, Leimgrubenweg 14, Ulm 89075, GermanyTel + 49 731 50045330Fax + 49 731 50045333Email marion.flechtner-mors@uni-ulm.deContext: It is questioned whether the potato protein protease inhibitor II (PI2) reduces appetite and exerts effects on the satiety hormone cholecystokinin (CCK).Objective: To investigate PI2 impact on gastrointestinal hormones and appetite measures during weight reduction.Design: In a randomized, placebo-controlled trial over 20 weeks, fifty-two overweight/obese participants (BMI 25.2– 38.0 kg/m 2) received a protein-rich diet (30%) adjusted to 500 kcal below their individual daily needs. Subjects ingested a capsule containing either PI2 (150 mg) or placebo twice daily 1 hr before lunch and dinner. At week 0 and week 10 participants joined breakfast test meals to determine CCK, GLP-1, ghrelin, leptin, glucose and insulin concentrations in a time course experimental manner. Appetite sensations were measured on test meal days and in week 4, 9, 14 and 19 using visual analogue scales.Results: Weight loss at week 10 and 20 in the PI2 group was 4.3± 3.1 kg and 5.6± 4.1 kg, in the control group: 4.7± 4.0 kg and 6.8± 3.7 kg. A significant effect of PI2 on circulating CCK levels was observed at week 10. The other hormones were unaffected by PI2. At week 10, PI2 group subjects showed higher satiety and decreased desire to eat compared to placebo. During study duration, PI2 showed a significant impact on appetite ratings prior to lunch, one hour before dinner and just before dinner.Conclusion: PI2 increased circulating CCK plasma levels during the diet intervention. Likewise, PI2 modulated appetite sensation from week 4 to 20. The study demonstrated that the PI2 can modulate a key satiety signal.Keywords: dietary supplement, appetite, satiety modification, obesity